A micro-mesoporous composite titanosilicate molecular sieve, a preparation method therefor and use thereof
By using bisimidazole-based multi-carbon chain quaternary ammonium salts as template agents to synthesize microporous composite titanium silicate borate molecular sieves, the problems of complex preparation and diffusion limitation in existing technologies have been solved, and high-efficiency catalytic performance and environmentally friendly olefin epoxidation and aldehyde-ketone ammoxidation reactions have been achieved.
Patent Information
- Application Number
- CN202310884661.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2043-07-19
AI Technical Summary
In the existing technology, the preparation steps of micro-mesoporous composite titanium-silicon molecular sieves are complex, difficult to control, and difficult to achieve stable and reproducible production. Furthermore, there are diffusion limitations in olefin epoxidation and aldehyde-ketone ammoxidation reactions, which affect the accessibility and utilization of the active center of the catalyst.
Using bisimidazole-based multi-carbon chain quaternary ammonium salt as an organic template agent, a micro-mesoporous composite molecular sieve containing titanium, silicon, and borate was synthesized by hydrothermal treatment under high temperature and high pressure. It has a unique micro-mesoporous structure and open pores, and is suitable for olefin epoxidation and aldehyde-ketone ammoxidation reactions.
It achieves high catalyst activity and stability, mild reaction conditions, few byproducts, meets the requirements of green chemistry, and broadens the application field of selective catalysis.
Smart Images

Figure CN116924430B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of inorganic chemical synthesis and chemical application technology, in particular to a micro-mesoporous composite titanium-containing silicate molecular sieve, a preparation method thereof and application of the catalyst in olefin epoxidation and aldehyde / ketone aminooxylation reactions. BACKGROUND
[0002] Zeolites are mainly crystalline materials with regular pore channels, which are connected by TO4(T = Si, Al, B, P, Ti and Sn, etc.) tetrahedral units through shared oxygen bridges to form a three-dimensional spatial network structure. Among them, titanium-containing silicate molecular sieves are widely used, which have high hydrogen peroxide activation ability, can realize the selective oxidation synthesis of various compounds under mild conditions to obtain high value-added oxygen-containing compounds, which is very consistent with the concept of "green chemistry" and meets the requirements of "atom economy". In the process of heterogeneous catalysis, the diffusion of substrate molecules mainly includes internal diffusion and external diffusion. For the olefin epoxidation and aldehyde / ketone oximation process catalyzed by the titanium silicate molecular sieve / H2O2 system, the influence of external diffusion can be eliminated by adjusting the stirring rate in the batch reactor, and the external diffusion limitation in the fixed bed reactor can be eliminated by adjusting the particle size of the catalyst. Therefore, for the titanium silicate molecular sieve / H2O2 system, it is very important to eliminate the internal diffusion of substrate molecules and improve the accessibility and utilization rate of Ti active centers.
[0003] At present, there are mainly three strategies to solve this problem: 1) Synthesis of titanium silicate molecular sieves with larger pore size to alleviate the diffusion limitation of substrate molecules. For example, Ti-Beta molecular sieves with three-dimensional 12-MR pores have greater catalytic oxidation ability for large molecular substrates such as cyclohexene and cyclohexane than TS-1 with 10-MR pores (Sci. Catal., 1990, 55, 43); Ti-UTL (Catal. Today, 2016, 277, 2) molecular sieves with 14-MR pores exhibit better catalytic activity than Ti-Beta molecular sieves with three-dimensional 12-MR pores in the cyclohexene epoxidation reaction (Appl. Catal. A: General., 2018, 550, 75). 2) Shorten the diffusion distance of substrate molecules in the molecular sieve pores, including adjusting the crystal morphology and size of the molecular sieve and synthesizing meso-microporous composite titanium silicate molecular sieves, etc. 3) Etching irregular mesoporous structures by post-treatment, etc. For example, using NaOH to treat Ti-MOR under hydrothermal conditions to prepare mesoporous Ti-MOR molecular sieves, the obtained samples exhibit much higher catalytic activity than the untreated Ti-MOR original sample in toluene hydroxylation reaction (J. Catal., 2011, 281, 263).
[0004] Existing technologies for preparing macroporous or microporous composite titanium-silicon molecular sieves have drawbacks such as complex preparation steps, difficulty in control, and difficulty in achieving stable and reproducible production. Therefore, there is an urgent need to develop a method for the direct hydrothermal synthesis of microporous composite titanium-silicon molecular sieves using a single template agent. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a microporous composite titanium-containing borosilicate molecular sieve, its preparation method, and its applications. Using a bisimidazole-based multi-carbon chain quaternary ammonium salt as an organic template agent, hydrothermal treatment under high temperature and high pressure conditions yields a microporous composite molecular sieve containing framework elements such as titanium, silicon, boron, and oxygen. Its composition is represented by B. x Ti y SiO z Let x be the molar ratio of B to Si, ranging from 0.2 to 1; y be the molar ratio of Ti to Si, ranging from 0.01 to 0.05; and z be the molar ratio of O to Si, where z = (3×x + 4×y + 4) / 2. This molecular sieve possesses a unique micro-mesoporous composite structure. Its first-order diffraction peak, representing the interlayer spacing, is located at 2.17°, indicating a mesoporous structure and open pore structure. It is suitable for catalyzing the epoxidation of olefins and the ammoxidation of aldehydes and ketones, synthesizing corresponding epoxides and oximes, respectively. It exhibits high product yields, meeting the "atom economy" requirements of green production of oxygen (nitrogen) chemicals and aligning with the concept of "green chemistry." In olefin epoxidation and aldehyde-ketone ammoxidation reactions, it demonstrates mild reaction conditions, environmental friendliness, good catalytic stability, high activity, and few byproducts. Its application in olefin epoxidation and aldehyde-ketone oxime reactions shows excellent catalytic performance, further broadening the research and application fields of selective catalysis.
[0006] The objective of this invention is achieved as follows: a microporous composite titanium-containing borosilicate molecular sieve, characterized by using titanium, silicon, boron, and oxygen as framework elements, and its molar composition expressed in anhydrous form as B. x Ti y SiO z , where x is the molar ratio of B to Si, ranging from 0.2 to 1; y is the molar ratio of Ti to Si, ranging from 0.01 to 0.05; z is the molar ratio of O to Si, and z = (3×x + 4×y + 4) / 2.
[0007] The characteristic spectral lines of the X-ray diffraction pattern of the microporous composite titanium-containing borosilicate molecules are shown in Table 1 below, Cu-Kα,
[0008] Table 1. X-ray diffraction structure data of microporous composite titanium silicate borate.
[0009]
[0010]
[0011] In the table: (a) is the relative intensity level of the diffraction peak in the powder X-ray diffraction spectrum, the specified value of the strongest diffraction peak is 100: W is less than 18 (weak); M is 18-45 (moderate); S is 45-60 (strong); VS is 60-100 (very strong).
[0012] A preparation method of a micro-mesoporous composite titanium-containing silicoborate molecular sieve, characterized in that the preparation method specifically comprises the following steps:
[0013] Step 1: mix a silicon source (calculated as SiO2), a titanium source (calculated as TiO2), a boron source (calculated as B2O3), an organic template agent and water in a molar ratio of 1.0:(0.005-0.1):(0.1-1):(0.1-2):(5-50), and stir at 80°C for 3-20 hours until a uniform mixed gel is obtained;
[0014] Step 2: transfer the uniform gel obtained in Step 1 into a high-temperature high-pressure reaction kettle, and crystallize at 140-170°C for 3-8 days; after crystallization is completed, wash with deionized water, and dry in an oven at 80-100°C for 8-20 hours to finally obtain a micro-mesoporous layered zeolite precursor;
[0015] Step 3: treat the micro-mesoporous layered zeolite precursor obtained in Step 2 with an acid solution, prepare a mixture of the molecular sieve precursor and the acid solution with a concentration of 2-6 mol / L according to a mass ratio of 1:(30-50), and treat at 120-150°C for 1-12 hours; after acidification, the precursor is filtered, washed, dried in an oven at 80-100°C for 8-20 hours, and finally calcined at 400-700°C for 1-24 hours to obtain a micro-mesoporous composite titanium-containing silicoborate molecular sieve, and the acid solution is an aqueous solution of oxalic acid, acetic acid, hydrochloric acid, sulfuric acid or nitric acid;
[0016] The organic template agent is a bis-imidazolyl polycarbon chain quaternary amine salt, and its structure is as follows:
[0017]
[0018] wherein R represents an alkyl chain containing 1-5 carbon atoms, and n=5-15.
[0019] The silicon source (calculated as SiO2), titanium source (calculated as TiO2), boron source (calculated as B2O3), organic template and water in the first step are mixed in a molar ratio of 1.0:(0.005-0.1):(0.1-1):(0.1-2):(5-50), wherein the silicon source is one or a mixture of two or more of tetraethyl orthosilicate, silica sol, silicic acid, white carbon black, fuming silica gel; the titanium source is one or a mixture of two or more of hexafluorotitanic acid, ammonium hexafluorotitanate, tetrabutyl titanate, titanium sulfate, titanium nitrate; and the boron source is one or a mixture of two or more of sodium borohydride, borax, boric acid, potassium borohydride, sodium borate.
[0020] The application of a micro-intermediate pore composite titanium-containing silicate borate molecular sieve, characterized in that the micro-intermediate pore composite titanium-containing silicate borate molecular sieve is used as a catalyst in an olefin epoxidation reaction, and the specific operation of the catalytic reaction is as follows:
[0021] First step: the reaction is carried out in a constant temperature water bath, and the reaction temperature is controlled at 40-80℃; the solvent, catalyst, reaction substrate and oxidant are sequentially added into a high-pressure resistant reaction tube, wherein the molar ratio of the reaction substrate / oxidant is 0.5-2, the mass ratio of the reaction substrate / catalyst is 15-35, and the mass ratio of the solvent / reaction substrate is 10-30; the solvent can be a protic solvent R-OH, wherein R=H or an alkyl group with 1-5 carbon atoms, or a non-protic solvent such as acetonitrile, benzene or benzonitrile; the oxidant is one or a mixture of two or more of hydrogen peroxide, tert-butyl hydroperoxide aqueous solution, tert-butyl hydroperoxide decane solution, ethylbenzene hydroperoxide ethylbenzene solution, cumene hydroperoxide cumene solution; and the reaction substrate is ethylene, propylene, n-hexene, n-heptene, n-octene, cyclopentene, cyclohexene, cycloheptene or cyclooctene.
[0022] Second step: the reaction mixture prepared in the first step is reacted at a temperature of 40-80℃ for 0.5-4 hours.
[0023] Third step: the high-pressure resistant reaction tube is placed in an ice water bath and cooled to 15-30℃, and the catalyst is removed by centrifugation to obtain an olefin epoxide product, which is analyzed by gas chromatography (Shimadzu 2014, FID detector).
[0024] The application of a micro-intermediate pore composite titanium-containing silicate borate molecular sieve, characterized in that the micro-intermediate pore composite titanium-containing silicate borate molecular sieve is used as a catalyst in an ammoxidation reaction of ketone aldehyde, and the specific operation of the catalytic reaction is as follows:
[0025] The first step: the reaction is carried out in a constant temperature water bath, and the reaction temperature is controlled at 40-80 DEG C, and the catalyst, the protic alcohol solvent, the ketone aldehyde containing organic compound, the ammonia source and the hydrogen peroxide are sequentially added into the high-pressure resistant reaction tube, the ketone aldehyde containing organic compound is mixed with the catalyst, the protic alcohol solvent, the ammonia source and the hydrogen peroxide according to the weight ratio of 1.0:0.02-0.40:5-20:0.2-1.0:0.1-1.0, the ketone aldehyde containing organic compound is acetaldehyde, propyl aldehyde, acetone, butanone or cyclohexanone; the solvent is water, t-butyl alcohol, methanol or ethanol; the ammonia source is one or a mixture of the two of ammonia gas and ammonia water.
[0026] The second step: the reaction temperature of the reaction mixture of the first step is increased to 40-80 DEG C and reacted for 1-5 hours.
[0027] The third step: the high-pressure resistant reaction tube is cooled to 15-30 DEG C in an ice water bath, and the catalyst is removed by centrifugation, the product is an oxime compound, the conversion rate and the selectivity of the product are analyzed by using a gas chromatograph (Shimadzu 2014, FID detector), and the catalytic activity is evaluated.
[0028] Compared with the prior art, the present application has the advantages of simple preparation process, novel structure, easy industrial production, environmentally friendly reaction process, meeting the requirements of green production of oxygen (nitrogen) chemicals "atomic economy", conforming to the concept of "green chemistry", and showing the characteristics of mild reaction conditions, environmental friendliness, good catalytic stability, high activity and less by-products in the olefin epoxidation and aldehyde ketone ammoxidation reactions, and excellent catalytic performance in the application of the olefin epoxidation and aldehyde ketone oximation reactions, which further widens the research and application fields of selective catalytic reactions. BRIEF DESCRIPTION OF DRAWINGS
[0029] Figure 1 The X-ray diffraction spectrum of the micro-mesoporous composite titanium-containing silicate borate molecular sieve prepared in Example 1;
[0030] Figure 2 The scanning electron microscope graph of the micro-mesoporous composite titanium-containing silicate borate molecular sieve prepared in Example 1;
[0031] Figure 3 The nitrogen adsorption-desorption curve distribution graph of the micro-mesoporous composite titanium-containing silicate borate molecular sieve prepared in Example 1. DETAILED DESCRIPTION
[0032] The following further details the preparation of the present application through specific examples. For brevity, only key technical data is listed for each step. All examples are operated according to the operation steps of the technical solution. Any simple modification and modification of the examples of the present application is within the scope of the technical solution of the present application. Any adjustment of the operation and conditions of the present application such as feed ratio, temperature, synthesis process, etc. is considered to be an infringement of the rights and interests of the present application.
[0033] Example 1
[0034] First step: mix silica sol (calculated as SiO2), tetrabutyl titanate (calculated as TiO2), boric acid (calculated as B2O3), organic template agent and water according to the molar ratio of 1.0:0.03:0.67:1.4:19, stir at 80°C for 6 hours until a uniform mixed gel is obtained, the organic structure directing agent is an organic structure directing agent with the following structural formula:
[0035]
[0036] Among them, R in the organic structure directing agent is methyl, and n is 6.
[0037] Second step: transfer the uniform gel obtained in the first step to a high temperature and high pressure reaction kettle, crystallize at 170°C for 7 days, and then wash with deionized water after crystallization is completed, and dry at 80°C for 12 hours, finally obtain a microporous layered zeolite precursor.
[0038] Third step: the microporous layered zeolite precursor obtained in the second step is treated with an acid solution, the microporous layered zeolite precursor and a 5 mol / L nitric acid solution are mixed according to a mass ratio of 1:35, and treated at a temperature of 140°C for 4h. The acid-treated precursor is filtered, washed, and dried at 80°C for 12 hours, and finally calcined at 500°C for 6 hours to obtain a microporous composite titanium-containing silicate borate molecular sieve.
[0039] Reference Figure 1 The microporous composite titanium-containing silicate borate molecular sieve prepared above is characterized by X-ray diffraction spectrum, and has good crystallinity, and has the X-ray diffraction structure data shown in Table 1, Cu-Kα,
[0040] Table 1 X-ray diffraction structure data of microporous composite titanium-containing silicate borate
[0041]
[0042]
[0043] In the table: (a) is the relative intensity level of the diffraction peak in the powder X-ray diffraction spectrum, the specified value of the strongest diffraction peak is 100; W is less than 18 (weak); M is 18-45 (moderate); S is 45-60 (strong); VS is 60-100 (very strong).
[0044] Referring to Figure 2 The micro-mesoporous composite titanosilicoborate molecular sieve prepared in Example 1 has a scanning electron microscope showing a sheet-type stacking morphology.
[0045] Referring to Figure 3 The micro-mesoporous composite titanosilicoborate molecular sieve prepared in Example 1 has a nitrogen adsorption-desorption curve showing a typical micro-mesoporous composite structure.
[0046] Example 2
[0047] First step: mix fumed silica (calculated as SiO2), hexafluorotitanic acid (calculated as TiO2), sodium borate (calculated as B2O3), an organic template and water in a molar ratio of 1.0:0.05:0.5:1.0:25, stir at 80°C for 12 hours until a uniform mixed gel is obtained, and the organic template is an organic structure directing agent with the following structural formula:
[0048]
[0049] In the organic structure directing agent, R is methyl, and n is 8.
[0050] Second step: transfer the uniform gel obtained in the first step to a high-temperature high-pressure reactor, crystallize at 150°C for 8 days, wash with deionized water after crystallization is complete, and dry at 80°C for 10 hours to obtain a micro-mesoporous layered zeolite precursor.
[0051] Third step: the micro-mesoporous layered zeolite precursor obtained in the second step is treated with an acid solution, and the micro-mesoporous layered zeolite precursor is mixed with a 4 mol / L oxalic acid solution in a mass ratio of 1:45, treated at 140°C for 6h, and the acidified precursor is filtered, washed, and dried at 90°C for 8 hours. Finally, the product is a micro-mesoporous composite titanosilicoborate molecular sieve after calcination at 550°C for 5 hours.
[0052] Example 3
[0053] The catalytic performance of the catalyst was evaluated by ethylene epoxidation reaction. The ethylene liquid phase epoxidation reaction was carried out in a sealed high-pressure resistant reaction tube, and the operation steps were as follows: 10 mL of acetonitrile was added into the high-pressure resistant reaction tube, then 100 mg of the catalyst, 10 mmol of ethylene and 15 mmol of tert-butyl hydroperoxide aqueous solution (70% by mass in water) were added in sequence. After the high-pressure resistant reaction tube was transferred into a 60°C water bath for reaction for 2 hours, the high-pressure resistant reaction tube was taken out and cooled to 20°C in an ice water bath, and the catalyst was removed by centrifugation. The filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector), and the ethylene conversion rate was 74.6%, and the selectivity of the target product ethylene oxide was 99.5%. The catalytic performance comparison of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve is shown in Table 2 below:
[0054] Table 2 Catalytic performance comparison of micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve
[0055] Ethylene conversion (%) Ethylene oxide selectivity (%) Example 3 74.6 99.5 Comparative Example 1 40.9 95.8
[0056] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Sci. Catal., 1990, 55, 43), and the SiO2 / TiO2 molar ratio was 30. The reaction conditions were the same as those in Example 3. The data by gas chromatography proved that the catalytic activity of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve used in Example 3 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the 1-hexene epoxidation reaction.
[0057] Example 4
[0058] The catalytic performance of the catalyst was evaluated by propylene epoxidation reaction. The propylene liquid phase epoxidation reaction was carried out in a sealed high-pressure resistant reaction tube, and the operation steps were as follows: 10 mL of cumene was added into the high-pressure resistant reaction tube, then 80 mg of the catalyst, 15 mmol of propylene and 10 mmol of cumene hydroperoxide cumene solution (80% by mass in cumene) were added in sequence. After the high-pressure resistant reaction tube was transferred into a 60°C water bath for reaction for 1 hour, the high-pressure resistant reaction tube was taken out and cooled to 25°C in an ice water bath, and the catalyst was removed by centrifugation. The filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector), and the propylene conversion rate was 58.8%, and the selectivity of the target product propylene oxide was 99.1%. The catalytic performance comparison of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve is shown in Table 3 below:
[0059] Table 3 Catalytic performance comparison of micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve
[0060] Propylene conversion (%) Propylene oxide selectivity (%) Example 4 58.8 99.1 Comparative Example 1 8.7 92.8
[0061] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Sci. Catal., 1990, 55, 43) with a SiO2 / TiO2molar ratio of 30, and the reaction conditions were the same as in Example 4. The data from gas chromatography proved that the catalytic activity of the microporous-mesoporous composite titanium-containing silicoborate molecular sieve used in Example 4 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the epoxidation of 1-hexene.
[0062] Example 5
[0063] The catalytic performance of the catalyst was evaluated by the epoxidation of 1-hexene. The liquid-phase epoxidation of 1-hexene was carried out in a sealed high-pressure reaction tube. The operation steps were as follows: 10 mL of acetonitrile, 50 mg of the catalyst, 10 mmol of 1-hexene, and 10 mmol of H2O2 (30% aqueous solution) were sequentially added to the high-pressure reaction tube. The high-pressure reaction tube was then transferred to a water bath at 60°C for reaction for 2 hours. After that, the high-pressure reaction tube was removed and placed in an ice water bath to cool to 20°C, and the catalyst was removed by centrifugation. The filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector). The conversion of 1-hexene was 50.7%, and the selectivity of the target product, n-hexene oxide, was 99.7%. The catalytic performance of the microporous-mesoporous composite titanium-containing silicoborate molecular sieve and the TS-1 titanium silicate molecular sieve was compared as shown in Table 4 below:
[0064] Table 4 Comparison of catalytic performance of microporous-mesoporous composite titanium-containing silicoborate molecular sieve and TS-1 titanium silicate molecular sieve
[0065] 1 -hexene conversion (%) N-hexene oxide selectivity (%) Example 5 50.7 99.7 Comparative Example 1 18.8 93.4
[0066] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Sci. Catal., 1990, 55, 43) with a SiO2 / TiO2molar ratio of 30, and the reaction conditions were the same as in Example 5. The data from gas chromatography proved that the catalytic activity of the microporous-mesoporous composite titanium-containing silicoborate molecular sieve used in Example 5 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the epoxidation of 1-hexene.
[0067] Example 6
[0068] The catalytic performance of the catalyst was evaluated by cyclohexene epoxidation reaction. The cyclohexene liquid phase epoxidation reaction was carried out in a sealed high-pressure resistant reaction tube. The operation steps were as follows: 10 mL of acetonitrile, 60 mg of the catalyst, 10 mmol of cyclohexene and 15 mmol of H2O2 (30% mass fraction aqueous solution) were sequentially added to the high-pressure resistant reaction tube, and the high-pressure resistant reaction tube was transferred to a 70°C water bath for reaction for 3 hours. After the reaction was completed, the high-pressure resistant reaction tube was removed and cooled to 15°C in an ice water bath, the catalyst was separated by centrifugation, and the filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector). The conversion rate of cyclohexene was 28.7%, the selectivity of the target product cyclohexene oxide was 87.9%, and the catalytic performance of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve and the TS-1 titanium silicate molecular sieve was compared as shown in Table 5 below:
[0069] Table 5 Comparison of catalytic performance of micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve
[0070] Cyclohexene conversion (%) Cyclohexene oxide selectivity (%) Example 6 28.7 87.9 Comparative Example 1 3.1 80.4
[0071] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Sci. Catal., 1990, 55, 43), and the SiO2 / TiO2 molar ratio was 30. The reaction conditions were the same as those of Example 6. The data by gas chromatography proved that the catalytic activity of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve used in Example 6 in the cyclohexene epoxidation reaction was much higher than that of the TS-1 catalyst used in Comparative Example 1.
[0072] Example 7
[0073] The catalytic performance of the catalyst was evaluated by cyclohexene epoxidation reaction. The operation steps were as follows: 10 mL of acetonitrile, 60 mg of the catalyst, 10 mmol of cyclohexene and 15 mmol of H2O2 (30% mass fraction aqueous solution) were sequentially added to the high-pressure resistant reaction tube, and the high-pressure resistant reaction tube was transferred to a 70°C water bath for reaction for 3 hours. After the reaction was completed, the high-pressure resistant reaction tube was removed and cooled to 15°C in an ice water bath, the catalyst was separated by centrifugation, and the filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector). The conversion rate of cyclohexene was 28.7%, the selectivity of the target product cyclohexene oxide was 87.9%, and the catalytic performance of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve and the TS-1 titanium silicate molecular sieve was compared as shown in Table 5 below:
[0074] Table 6 Comparison of catalytic performance of micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve
[0075] Cyclooctene conversion (%) Cyclooctene oxide selectivity (%) Example 7 10.8 68.7 Comparative Example 1 1.7 59.7
[0076] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Sci. Catal., 1990, 55, 43) with a SiO2 / TiO2molar ratio of 30, and the reaction conditions were the same as in Example 7. The data from gas chromatography proved that the catalytic activity of the micro-mesoporous composite titanium-containing silicoborate molecular sieve used in Example 7 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the epoxidation of cyclooctene.
[0077] Example 8
[0078] The catalytic performance of the catalyst was evaluated by the acetone ammoximation reaction. The catalyst, tert-butyl alcohol, acetone, ammonia and hydrogen peroxide were sequentially added to a high-pressure resistant reaction tube, and the acetone, catalyst, tert-butyl alcohol, ammonia and hydrogen peroxide were mixed at a weight ratio of 1.0:0.1:10:0.25:0.4. The above reaction solution was stirred at 70°C for 60 minutes. After the reaction was completed, the high-pressure resistant reaction tube was removed and cooled to 25°C in an ice water bath, and the catalyst was separated by centrifugation. The filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector). The conversion rate of acetone was 29.6%, and the selectivity of the target product acetone oxime was 82.7%. The catalytic performance of the micro-mesoporous composite titanium-containing silicoborate molecular sieve and the TS-1 titanium silicate molecular sieve is shown in Table 7 below:
[0079] Table 7 Comparison of catalytic performance of micro-mesoporous composite titanium-containing silicoborate molecular sieve and TS-1 titanium silicate molecular sieve
[0080] Acetone conversion (%) Acetone oxime selectivity (%) Example 8 29.6 82.7 Comparative Example 1 17.4 78.1
[0081] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Sci. Catal., 1990, 55, 43) with a SiO2 / TiO2molar ratio of 30, and the reaction conditions were the same as in Example 8. The data from gas chromatography proved that the catalytic activity of the micro-mesoporous composite titanium-containing silicoborate molecular sieve used in Example 8 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the acetone ammoximation reaction.
[0082] Example 9
[0083] The catalytic performance of the catalyst was evaluated by butanone ammoximation reaction. The catalyst, tert-butyl alcohol, butanone, ammonia and hydrogen peroxide were sequentially added into a high-pressure resistant reaction tube, and the butanone was mixed with the catalyst, tert-butyl alcohol, ammonia and hydrogen peroxide at a weight ratio of 1.0:0.05:15:0.25:0.3. The above reaction solution was stirred at 70°C for 2 hours. After the reaction was completed, the high-pressure resistant reaction tube was taken out and cooled to 20°C in an ice water bath, centrifuged and separated from the catalyst. The filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector). The conversion rate of butanone was 96.8%, and the selectivity of the target product butanone oxime was 99.7%. The catalytic performance of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve is shown in Table 8 below:
[0084] Table 8 Comparison of catalytic performance of micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve
[0085] Butanone conversion (%) Butanone oxime selectivity (%) Example 9 96.8 99.7 Comparative Example 1 74.5 89.8
[0086] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Sci. Catal., 1990, 55, 43), and the SiO2 / TiO2 molar ratio was 30. The reaction conditions were the same as those in Example 9. The data by gas chromatography proved that the catalytic activity of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve used in Example 9 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the butanone ammoximation reaction.
[0087] Example 10
[0088] The catalytic performance of the catalyst was evaluated by cyclohexanone ammoximation reaction. The catalyst, tert-butyl alcohol, cyclohexanone, ammonia and hydrogen peroxide were sequentially added into a high-pressure resistant reaction tube, and the cyclohexanone was mixed with the catalyst, tert-butyl alcohol, ammonia and hydrogen peroxide at a weight ratio of 1.0:0.3:5:0.3:0.6. The above reaction solution was stirred at 60°C for 3 hours. After the reaction was completed, the high-pressure resistant reaction tube was taken out and cooled to 25°C in an ice water bath, centrifuged and separated from the catalyst. The filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector). The conversion rate of cyclohexanone was 99.8%, and the selectivity of the target product cyclohexanone oxime was 99.7%. The catalytic performance of the micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve is shown in Table 9 below:
[0089] Table 9 Comparison of catalytic performance of micro-mesoporous composite titanium-containing silicate-borate molecular sieve and TS-1 titanium silicate molecular sieve
[0090] Cyclohexanone conversion (%) Cyclohexanone oxime selectivity (%) Example 10 99.1 99.3 Comparative Example 1 87.4 99.2
[0091] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method described in the literature (Sci. Catal., 1990, 55, 43) with a SiO2 / TiO2molar ratio of 30, and the reaction conditions were the same as those of Example 10. The data obtained by gas chromatography proved that the catalytic activity of the micro-mesoporous composite titanium-containing silicoborate molecular sieve used in Example 10 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the cyclohexanone ammoximation reaction.
[0092] Example 11
[0093] The catalytic performance of the catalyst was evaluated by acetaldehyde ammoximation reaction. The catalyst, t-butyl alcohol, acetaldehyde, ammonia and hydrogen peroxide were sequentially added to a high-pressure resistant reaction tube, and the acetaldehyde, catalyst, t-butyl alcohol, ammonia and hydrogen peroxide were mixed at a weight ratio of 1.0:0.3:20:0.5:0.3. The above reaction solution was stirred at 80°C for 4 hours. After the reaction was completed, the high-pressure resistant reaction tube was cooled to 25°C in an ice water bath, the catalyst was separated by centrifugation, and the filtrate was analyzed by gas chromatography (Shimadzu 2014, FID detector). The conversion rate of acetaldehyde was 73.4%, and the selectivity of the target product acetaldehyde oxime was 81.5%. The catalytic performance of the micro-mesoporous composite titanium-containing silicoborate molecular sieve and the TS-1 titanium silicate molecular sieve is shown in Table 10 below:
[0094] Table 10 Comparison of catalytic performance of micro-mesoporous composite titanium-containing silicoborate molecular sieve and TS-1 titanium silicate molecular sieve
[0095] Acetaldehyde conversion (%) Acetaldehyde oxime selectivity (%) Example 11 73.4 81.5 Comparative Example 1 64.4 68.7
[0096] The TS-1 catalyst used in Comparative Example 1 was synthesized according to the method described in the literature (Sci. Catal., 1990, 55, 43) with a SiO2 / TiO2molar ratio of 30, and the reaction conditions were the same as those of Example 11. The data obtained by gas chromatography proved that the catalytic activity of the micro-mesoporous composite titanium-containing silicoborate molecular sieve used in Example 11 was much higher than that of the TS-1 catalyst used in Comparative Example 1 in the acetaldehyde ammoximation reaction.
[0097] The micro-mesoporous composite titanium-containing silicoborate molecular sieve used in Examples 3-11 was used as a catalyst in the catalytic epoxidation of olefins and the oximation of aldehydes and ketones, and the reaction products were analyzed by gas chromatography (Shimadzu 2014, FID detector) and found to exhibit excellent catalytic activity.
[0098] The protection scope of the present application is not limited to the above examples, and any changes and advantages that can be conceived by those skilled in the art without departing from the spirit and scope of the present application are included in the present application, and are protected by the appended claims.
Claims
1. A micro-mesoporous composite titanosilicate molecular sieve, characterized by, The molecular sieve is a micro-mesoporous composite titanium-containing silicate borate molecular sieve composed of titanium, silicon, boron and oxygen as framework elements, and its oxide composition in anhydrous form is represented as: B x Ti y SiO z wherein x is the molar ratio of B to Si, x is in the range of 0.2 to 1; y is the molar ratio of Ti to Si, y is in the range of 0.01 to 0.05; z is the molar ratio of O to Si, and z = (3x + 4y + 4) / 2; the micro-mesoporous composite titanium-containing silicate borate molecular sieve has the X-ray diffraction data of the diffraction peaks shown in Table 1 below: Cu-Ka, λ = 1.5406 Å: Table 1 X-ray diffraction data of the micro-mesoporous composite titanium-containing silicate borate ; In the table: (a) is the relative intensity level of the diffraction peak in the powder X-ray diffraction pattern, W is the weak level diffraction peak less than 18; M is the medium level diffraction peak of 18 ~ 45; S is the strong level diffraction peak of 45 ~ 60; VS is the strongest level diffraction peak of 60 ~ 100.
2. A method for preparing the micro-mesoporous composite titanosilicate molecular sieve of claim 1, characterized in that, The preparation of the micro-mesoporous composite titanium-containing silicate borate molecular sieve specifically includes the following steps: Step a: mix the silicon source calculated as SiO2, titanium source calculated as TiO2, boron source calculated as B2O3, organic template agent and deionized water in a molar ratio of 1.0:0.005~0.1:0.1~1:0.1~2:5~50, stir at a temperature of 80 ℃ for 3~20 hours, and obtain a uniformly mixed gel, wherein the silicon source is one or a mixture of two or more of tetraethyl orthosilicate, silica sol, silicic acid, white carbon black, fuming silica gel; the titanium source is one or a mixture of two or more of hexafluorotitanic acid, ammonium hexafluorotitanate, tetrabutyl titanate, titanium sulfate, titanium nitrate; the boron source is one or a mixture of two or more of sodium borohydride, borax, boric acid, potassium borohydride, sodium borate; the organic template agent is a bis-imidazole-based polycarbon chain quaternary amine salt with the following structure: ; Wherein: R is an alkyl chain containing 1~5 carbon atoms; n = 5~15; Step b: crystallize the above-prepared gel at a temperature of 140~170 ℃ for 3~8 days, wash the crystallized product with deionized water, and dry at a temperature of 80~100 ℃ for 8~20 hours to obtain a micro-mesoporous layered zeolite precursor; Step c: mix the above-prepared micro-mesoporous layered zeolite precursor with an acid solution with a concentration of 2~6 mol / L in a mass ratio of 1:30~50, acidize at a temperature of 120~150 ℃ for 1~12 hours, filter and wash the acidized precursor, dry at a temperature of 80~100 ℃ for 8~20 hours, and then calcine at a temperature of 400~700 ℃ for 5~24 hours to obtain the product, which is a micro-mesoporous composite titanium-containing silicate borate molecular sieve, and the acid solution is an aqueous solution of oxalic acid, acetic acid, hydrochloric acid, sulfuric acid or nitric acid.
3. The use of the micro-mesoporous composite titanosilicate molecular sieve according to claim 1, characterized in that, The micro-mesoporous composite titanium-containing silicate borate molecular sieve is used as a catalyst in olefin epoxidation reaction and ammoxidation reaction of ketone aldehyde, and the specific steps of the catalytic reaction are as follows: a step: the olefin substrate is mixed with solvent, catalyst and oxidant, the molar ratio of the oxidant to the olefin substrate is 1:0.5 ~ 2; the mass ratio of the catalyst to the olefin substrate is 1:15 ~ 35; the mass ratio of the olefin substrate to the solvent is 1:10 ~ 30; the solvent is a protic solvent of R-OH, wherein R = H or an alkyl group with 1 ~ 5 carbon atoms, or an aprotic solvent of acetonitrile, benzene, benzonitrile; the oxidant is one of hydrogen peroxide, tert-butyl hydroperoxide aqueous solution, tert-butyl hydroperoxide decane solution, ethylbenzene hydroperoxide ethylbenzene solution, cumene hydroperoxide cumene solution, or a mixture of two or more thereof; the olefin substrate is ethylene, propylene, n-hexene, n-heptene, n-octene, cyclopentene, cyclohexene, cycloheptene or cyclooctene; b step: the mixture is reacted at a temperature of 40 ~ 80 ℃ for 0.5 ~ 4 hours; c step: the reaction is cooled to 15 ~ 30 ℃, the catalyst is removed by centrifugation, and the product is an olefin epoxide; The micro-mesoporous composite titanium-containing silicate borate molecular sieve is a catalyst for the ammoxidation reaction of ketone aldehyde, and the specific steps of the catalytic reaction are as follows: a step: the aldehyde ketone substrate is mixed with catalyst, solvent, ammonia source and hydrogen peroxide at a weight ratio of 1.0:0.02 ~ 0.40:5 ~ 20:0.2 ~ 1.0:0.1 ~ 1.0, the aldehyde ketone substrate is acetaldehyde, propionaldehyde, acetone, butanone or cyclohexanone; the solvent is deionized water, tert-butyl alcohol, methanol or ethanol; the ammonia source is ammonia gas or ammonia water; b step: the mixture is reacted at a temperature of 40 ~ 80 ℃ for 1 ~ 5 hours; c step: the reaction is cooled to 15 ~ 30 ℃, the catalyst is removed by centrifugation, and the product is an oxime compound.
Citation Information
Patent Citations
Method for preparing EUO structural zeolite
CN103183354A
ECNU-30 molecular sieve as well as preparation method and catalytic application thereof
CN116332202A
Titanium-silicon molecular screen ECNU-2 and synthesizing method thereof
CN1654329A